Properties of Modified Double Laplace Transforms and Special Functions - Borawake, V. K.; Hiwarekar, A. P. (Communications in Mathematics and Applications, 2024)
This paper deals with new results on modified double Laplace transforms and special functions. Starting with basic definitions and results, we have obtained a modified double Laplace transform of unit step functions, and periodic functions and developed new theorems. Finally, we illustrate our results with examples.
Keywords: Laplace transform; Multiple integral transforms; Integral transform of special functions; Double Laplace transform; Convolution